Nepalese Customers’ Attitude and Preferences towards Online Marketing: Index Based Analysis - Seeprata Parajuli; Aayush Bijukshe; Niranjan Devkota; Udbodh Bhandari; Udaya Poudel (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Tremendous evolution of virtual advertising and marketing has also made its effect in Nepal as it is making around the globe. Current status of e-trade in Nepal seems to be promisingly accurate as many customers are being attracted to online purchasing and using online offerings. With the advent of latest technologies, virtual stores, and interactive apps, there is a huge boost in area of e-commerce. This study, therefore, aims to analyze Nepalese customers’ attitudes and preferences towards online marketing. A descriptive research design has been applied for this study where a sample of 401 respondents was taken in Kathmandu valley. Both Attitude and Preferences Index were a measure to check respondents' attitude level and preferences level respectively towards online marketing in Kathmandu valley. The current study found that 55% of consumers believe online marketing provides informative content to them. The majority of consumers have a positive attitude towards online marketing and they are preferring to purchase via online websites if they improve on certain criteria. The study also shows that customers are aware and satisfied regarding online marketing. However, 28.43% feel that there are still some challenges in the online marketing sector in Nepal that can be mitigated with the implementation of effective strategies. Thus, the study concludes that concerned authorities and online business holders should pay proper attention to the challenges faced by consumers so that they could be mitigated so that consumers would have a better online purchase experience.